A randomised, open label phase III trial with nimotuzumab, an anti-epidermal growth factor receptor monoclonal antibody in the treatment of newly diagnosed adult glioblastoma. Issue 4 (March 2015) - Westphal, Manfred; Heese, Oliver; Steinbach, Joachim P.; Schnell, Oliver; Schackert, Gabriele; Mehdorn, Maximilian; Schulz, Dirk; Simon, Matthias; Schlegel, Uwe; Senft, Christian; Geletneky, Karsten; Braun, Christian; et al.
Abstract: Purpose: A randomised, open label phase III trial was conducted to evaluate efficacy of nimotuzumab, a monoclonal antibody against epidermal growth factor receptor (EGF-R) added to standard therapy for newly diagnosed glioblastoma. Patients and methods: 149 glioblastoma patients stratified as with or without residual tumour were randomly assigned to receive either intravenous nimotuzumab 400 mg weekly added to standard radiochemotherapy followed by 400 mg biweekly after twelve weeks or standard radiochemotherapy. Progression status after 52 weeks (12moPFS) and progression-free survival (PFS) based on Macdonald criteria were co-primary and overall survival (OS), toxicity and quality of life secondary end-points. Results: 142 patients were evaluated for efficacy (per protocol cohort). 12moPFS was 25.6% in the experimental arm and 20.3% in the control group. In residual tumour patients ( n = 81) median PFS was 5.6 versus 4.0 months, (hazard ratio (HR), 0.87; 95% confidence interval (CI), 0.55–1.37), for patients without residual tumour ( n = 61) it was 10.6 versus 9.9 months, (HR, 1.01; 95% CI, 0.57–1.77). Median OS in patients with residual tumour was 19.5 versus 16.7 months, (HR, 0.90; 95% CI, 0.52–1.57; P = 0.7061), for patients without 23.3 versus 21.0 months (HR, 0.77; 95% CI, 0.41–1.44; P = 0.4068). A small cohort of MGMT non-methylated patients with residual tumour showed PFS of 6.2 versus 4.0 months (HR, 0.77; 95% CI, 0.35–1.67; P = 0.4997) and OS of 19.0 versus 13.8 months (HR, 0.66; 95% CI, 0.27–1.64; P = 0.3648). EGF-R amplification did not correlate with clinical efficacy of nimotuzumab. Nimotuzumab was well tolerated. Conclusion: This study, albeit negative, contains hypothesis generating signals supporting evaluation of correlative, efficacy-predicting tumour parameters for nimotuzumab in the treatment of glioblastoma.